2016
DOI: 10.1080/03079457.2016.1139688
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of necrotic enteritis in chickens: what we know and what we need to know: a review

Abstract: This review summarizes advances in understanding the pathogenesis of necrotic enteritis of chickens caused by netB-positive Clostridium perfringens. The discovery of NetB as the essential toxin trigger for the disease was followed by recognition that it forms part of a large plasmid-encoded 42 kb pathogenicity locus (NELoc-1). While the locus is critical for toxin production, it likely has additional functions related to colonization and degradation of the mucus barrier, which are essential both to multiplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
131
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 41 publications
3
131
0
4
Order By: Relevance
“…Although many studies have been conducted to better describe the role of C. perfringens in necrotic enteritis pathogenesis, little work has been done to better characterize this microorganism population structure in commercial broiler chicken farms, where the use of antimicrobials has been discontinued (Prescott et al, 2016; Rood et al, 2016). More importantly, much remains to be explained to better understand why raising drug-free birds would be more challenging on some farms in regard to digestive health management and NE issues (Brady et al, 2010; Smith, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have been conducted to better describe the role of C. perfringens in necrotic enteritis pathogenesis, little work has been done to better characterize this microorganism population structure in commercial broiler chicken farms, where the use of antimicrobials has been discontinued (Prescott et al, 2016; Rood et al, 2016). More importantly, much remains to be explained to better understand why raising drug-free birds would be more challenging on some farms in regard to digestive health management and NE issues (Brady et al, 2010; Smith, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that C. perfringens strains associated with NE outbreaks would not only possess a chromosomal genetic background conferring them a selective advantage over the commensal strains (Chalmers et al, 2008; Hibberd et al, 2011; Lepp et al, 2013; Lacey et al, 2016), but that these strains would also harbor many plasmid-borne virulence genes organized in pathogenicity loci (Lepp et al, 2010; Lacey et al, 2016). Within these loci, some genes encoding toxins, antibiotic resistance, and adhesion factors might preferentially contribute to the ability of the virulent strains to persist over time and to colonize the birds (Lacey et al, 2016; Prescott et al, 2016; Zhou et al, 2017). Indeed, some genes found in these strains could be associated with a better adaptation to an environment where the disease is raging and where they will find the conditions to undergo positive selection and multiplication (Sawires and Songer, 2006; Prescott et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QS systems related to the S. aureus Agr system are widespread among Firmicutes (31) and typically act to regulate concerted, populationwide behaviors such as sporulation, biofilm formation, and virulence (32)(33)(34). The development of NE in poultry is generally attributed to the rapid overgrowth of C. perfringens in the gut and subsequent elaboration of virulence factors that induce damage to the host (35,36), a progression that is consistent with a QS-based regulatory mechanism. It follows that, by coordinating the production of extracellular toxins and enzymes to occur only once a sufficient population density is reached, a pathogen may inflict the greatest damage to the host while at the same time minimizing its expenditure of metabolic resources.…”
Section: Discussionmentioning
confidence: 99%
“…A third alternative explanation for the CP1⍀agrB attenuated in vivo virulence that does not involve NetB is the requirement of other agr-regulated genes for NE patho- genesis, although a more likely scenario is that additional agr-regulated genes contribute to virulence alongside NetB. Recent advances have made it clear that the onset of NE is a complex process involving multiple C. perfringens virulence factors related to colonization, adhesion, and acquisition of nutrients (35). Global gene expression analysis of CP1⍀agrB revealed 66 genes that were significantly differentially expressed compared to the wild-type CP1 control.…”
Section: Discussionmentioning
confidence: 99%